Comparison of Fine Needle Aspiration Cytology andHistopathology in diagnosing malignant thyroid swellings: Experience from a Tertiary Care Centre of Tripura, India - Biswanath Das; Tarun Guha,; Shatabdi Pal (Global Journal of Medicine and Public Health)
Background